Electrospun nanocomposite materials for polymer electrolyte membrane methanol fuel cells - Awang, N. (Springer International Publishing, 2017)
Recently, the demands of modern society on energy have become enormous. This consequently rises up significant concerns on the ecological and environmentally friendly energy conversion to power up applications from portable devices up to stationary power plant. Direct methanol fuel cell (DMFC) is one of the zero-pollution energy supply fuel cells that has gained much attention for their high efficiency and high power density yet compact in size. In order to ensure a continuously high performance power output from DMFC, a promising proton exchange membrane (PEM) with high proton conductivity and low methanol permeability is desirable. As one of the most promising and versatile fabrication methods for one-dimensional microstructure nanomaterials composed of organic and inorganic components prepared as randomly arranged continuous nanofibrous mats, electrospinning has been widely investigated to fabricate PEM applied in DMFC because of their dimensional, directional, and compositional flexibility. In this chapter, the application of electrospun nanofibers from organic, inorganic, and composite organic-inorganic is reviewed in details. Particular progresses with the use of electrospun nanofibers to improve fuel cell performance in terms of power density, ionic conductivity, interfacial resistance, and chemical stability, as well as mechanical strength are emphasized and discussed. The meaningful critical review could contribute to further enhance the development and evolution of fuel cells as one of the advanced energy conversion systems.